Impact of Collared Peccaries Dycotiles tajacu (Artiodactyla: Tayassuidae) on understory vegetation in the tropical rainforest of the Nogal-La Selva Biological Corridor, Costa Rica - Osorto Nuñez, Marco Herminio (2024)
Introduction: Evidence suggests that herbivores, such as peccaries, shape vegetation structure and diversity through predation, trampling, dispersal, and rooting behavior. Objective: To evaluate the impact of peccaries (Dycotiles tajacu) on the understory vegetation of the tropical rainforest in the Nogal-La Selva Local Biological Corridor, Costa Rica, comparing a site with the absence of peccaries to another with the presence of these animals. Methodology: From June to November 2021, 20 experimental exclusions and 20 free access plots, each measuring 2 m2 were used to quantify herbivory, the number of leaf blades, damaged leaves, healthy leaves, sapling height, and fallen biomass at both sites. Results: A higher sapling density was found in the Nogal Reserve, but a lower sapling diversity, while in La Selva there was a higher sapling diversity, but a lower density of seedlings. Herbivory and sapling height in La Selva exceeded those in Nogal. The exclusion of peccaries reduced seedling damage but did not affect the dynamics of fallen biomass. Conclusion: For the design, implementation, and evaluation of the effectiveness of biological corridors, it is crucial to consider plant-animal interactions to enhance the flow of ecological processes through functional and structural connectivity, analyzed from interactions such as those presented in this paper.